2020
DOI: 10.1038/s41598-020-70298-2
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally high strain-hardening and ductility due to transformation induced plasticity effect in Ti-rich high-entropy alloys

Abstract: Their experimental observations confirmed the Bo-Md approach could be useful in terms of designing new Ti-rich BCC-HEAs. It should be noted however, the relevance and validity of these predictions based on this controlled alloy strategy for other alloys is not yet fully explored. The primary objective of the present study is to investigate deformation mechanisms of new Ti-rich BCC-HEAs designed using the Bo-Md approach. Given the vast compositional space of HEAs, appropriate alloying elements must be chosen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 42 publications
(65 reference statements)
0
14
0
1
Order By: Relevance
“…On the other hand, the Laves phase with a C14 structure are forming above 1.40 values of Md Ti . The analysis Bo–Md diagrams from [ 29 , 30 , 31 , 32 , 33 , 34 ] allows us to state that a Ti-based BCC structure occurs with Md values much higher, even above 2.5, which is evidently dependent of Bo values. Sheikh et al [ 35 ] suggest that border the Md parameter that characterizes precipitations in Fe-M or Cr-M can be used in HEA with dominant Ti content; however, the alloy composition should include iron and chromium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the Laves phase with a C14 structure are forming above 1.40 values of Md Ti . The analysis Bo–Md diagrams from [ 29 , 30 , 31 , 32 , 33 , 34 ] allows us to state that a Ti-based BCC structure occurs with Md values much higher, even above 2.5, which is evidently dependent of Bo values. Sheikh et al [ 35 ] suggest that border the Md parameter that characterizes precipitations in Fe-M or Cr-M can be used in HEA with dominant Ti content; however, the alloy composition should include iron and chromium.…”
Section: Resultsmentioning
confidence: 99%
“…The correctness of this method for the analysis of the martensitic transformation in titanium alloys was also confirmed in numerous studies analyzing phase transformations in conventional titanium alloys [ 24 , 29 , 30 , 31 ]. This concept was also used for the analysis of the phase transformation-induced plasticity (TRIP) occurring in high-entropy alloys with dominant titanium content [ 32 , 33 , 34 ]. It should be noted, however, that these works concern the changes that occurred in the conventional alloys with a solid solution structure without the precipitation of other phases, such as the Laves phase.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the prognostication of deformation features of β alloys, the Bo-Md diagram also delineates the regions with the α and α+β structures. Several recent studies showed reasonable applicability of the Bo-Md diagram for Ti-containing HEAs demonstrating TRIP or MBIP effects [67][68][69][70]. Therefore, we reconstructed the Bo-Md diagram, collected numerous Ti-containing HEAs with either TRIP or MBIP effect, and several Ti alloys (Fig.…”
Section: Analysis Of Alloy Composition Using D-electron Approachmentioning
confidence: 99%
“…Studies of HEAs initially focused on as-cast single-phase alloys, for many of which it appeared difficult to reach a good balance of strength and ductility, as desired for industrial applications. Therefore, research has broadened to multiphase HEAs to explore precipitation strengthening [6][7][8][9][10][11], transformation-induced plasticity (TRIP) [12][13][14][15][16][17] and eutectic/eutectoid systems [18][19][20]. In particular, a combination of a comparatively high strength and high ductility was observed in ingots of an AlCoCr-FeNi 2.1 eutectic high-entropy alloy (EHEA) [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%